Diagnostic accuracy of perinatal post-mortem ultrasound (PMUS): a systematic review. Issue 1 (11th November 2019) - Shelmerdine, Susan; Langan, Dean; Sebire, Neil J; Arthurs, Owen
Abstract : Objective: Ultrasound is ubiquitous in live paediatric imaging; however, its usage in post-mortem setting is less established. This systematic review aims to evaluate the diagnostic accuracy of paediatric post-mortem ultrasound (PMUS). Design: MEDLINE, Embase and Cochrane Library databases were queried for studies published between 1998 and 2018 assessing PMUS diagnostic accuracy rates in children<18 years old, using autopsy as reference standard. Risk of bias was assessed using Quality Assessment of Diagnostic Accuracy Studies 2. A bivariate random-effects model was used to obtain combined mean estimates of sensitivity and specificity for different body systems. Results: Four studies were included, all relating to ultrasound for perinatal deaths. The mean diagnostic sensitivity and specificity for neurological abnormalities were 84.3% (95% CI: 70.8% to 92.2%) and 96.7% (95% CI: 86.5% to 99.3%); for cardiothoracic abnormalities 52.1% (95% CI: 27.6% to 75.5%, ) and 96.6% (95% CI: 86.8% to 99.2%); and for abdominal abnormalities 78.4% (95% CI: 61.0% to 89.4%) and 97.3% (95% CI: 88.9% to 99.4%). Combining all body systems, the mean sensitivity and specificity were 73.3% (95% CI: 59.9% to 83.5%) and 96.6% (95% CI: 92.6% to 98.4%). Conclusions: PMUS demonstrates a reasonable diagnostic accuracy, particularly for abdominal and neurological abnormalities, although cardiac anomalies were less readily identified. Trial registration number: CRD42018106968.